'I'm Crushing Your Binaries!' Drag in Monty Python and Kids in the Hall. Issue 2 (2nd July 2016) - Whybray, Adam
ABSTRACT: Monty Python (1969–1974) and Kids in the Hall (1988–1994) are two male comedy sketch show troupes well known for performing as women. Through analysis of the performance styles present in Monty Python and Kids in the Hall sketches, we can observe a shift from a camp to a queer sensibility. Esther Newton's Mother Camp (1972) and Judith Butler's Gender Trouble (1990) were released, respectively, during the broadcast of each show and provide a critical framework through which the subversiveness of a given act of drag can be evaluated. Female impersonation in Monty Python's Flying Circus is signified by handbags, permed hair and voices that alternate between shrill and husky. Gender transformation is achieved through the foregrounding of token signifiers that hyperbolically represent femininity, but do not attempt to approximate it. By contrast, the more nuanced female impersonation in Kids in the Hall reconfigures the gender of the performers to achieve a queering effect. Using Newton and Butler to define and illustrate the difference between these two modes of performance, the subversive/conservative value of both (as enacted in the shows) will be evaluated.